The examination of mini trampoline training programs planned with different diet regimens according to selected variables - KİRİŞCİ, İLKER (My University, 2023)
The aim of this research is to investigate the effects of short-term high carbohydrate and high protein diet programs on the speed, endurance performance, and body composition of participants with mini trampoline training. The research was approved by the ethics committee of Istanbul Gelisim University on 18.08.2022, with decision number 2022-13 in the meeting 23-01-36. Participants included 15 male volunteers who were students of Istanbul Gelisim University School of Physical Education and Sports and participated in mini trampoline training. Participants were divided into three groups: high carbohydrate diet group (n:5), high protein diet group (n:5), and control group (n:5). As a pre-test, participants' body composition measurements and endurance (30-15IFT) and 20-meter sprint tests from motor skills were conducted. Personalized diet programs were created for the high carbohydrate diet group with a ratio of 70% carbohydrates, 10% protein, and 20% fat, and for the high protein diet group with a ratio of 30% carbohydrates, 35% protein, and 35% fat. Participants were asked to perform mini trampoline training regularly twice a week and follow their diet programs for 2 days before the final test. SPSS 17 package program was used for data analysis. Tests for body composition and motor skills were analyzed using ANOVA. As a result, the high carbohydrate diet programming applied with mini trampoline training resulted in a decrease in body composition parameters, but this difference was not found to be significant. In the high protein diet application, although an increase was observed in VO2max and 20-meter sprint running test values obtained from the 30-15IFT endurance test, no significant difference was detected.
Keywords: Carbohydrate; protein; trampoline gymnastics; 30-15IFT; speed